Mothers at risk : exploring risk awareness and management of stay-at-home mothers in Singapore - Sheril Amilia Amir (2018)
Based on 30 in-depth interviews with stay-at-home mothers (SAHM), this article examines the old-age risk awareness of these mothers by class categories, and how gender intersects with class positions to determine the type of risk management strategies that were adopted to achieve feelings of security in a risk society. The women in this study tended to use their social and economic advantage in gendered ways, reinforcing the gender ideals that originally led to their exit from the formal economy. Upper-class SAHM are also similarly vulnerable to middle-class SAHM despite having more resources, caused by the false sense of security from their current circumstances. By examining the intersections of class and gender in risk management and awareness, it provides us with a more holistic picture of the true vulnerabilities that these mothers face in the Singapore society today.